2001
DOI: 10.1046/j.1537-2995.2001.41010106.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of non‐ABO RBC alloantibodies in patients undergoing allogeneic HPC transplantation. Is ABO incompatibility a predisposing factor?

Abstract: Patients undergoing allogeneic HPC transplantation are at risk of developing RBC-specific antibodies despite the immunosuppressive therapy administered. Antibody formation was more frequently observed in ABO-mismatched cases, which suggests a potential role of this incompatibility in facilitating antibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…Patients undergoing BMT are at risk for alloimmunization and hemolysis [5,44,45]. Although BMT patients are profoundly immunosuppressed after myeloablation, minor RBC antibodies may occur either as a result of passenger lymphocytes from the graft [44,46], myeloablation-resistant host lymphocytes [5,46], or a primary alloimmune response to RBC transfusion [45,46].…”
Section: Incidence Of Minor Rbc Antigen Alloimmunization In Various Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients undergoing BMT are at risk for alloimmunization and hemolysis [5,44,45]. Although BMT patients are profoundly immunosuppressed after myeloablation, minor RBC antibodies may occur either as a result of passenger lymphocytes from the graft [44,46], myeloablation-resistant host lymphocytes [5,46], or a primary alloimmune response to RBC transfusion [45,46].…”
Section: Incidence Of Minor Rbc Antigen Alloimmunization In Various Cmentioning
confidence: 99%
“…Although BMT patients are profoundly immunosuppressed after myeloablation, minor RBC antibodies may occur either as a result of passenger lymphocytes from the graft [44,46], myeloablation-resistant host lymphocytes [5,46], or a primary alloimmune response to RBC transfusion [45,46]. In the event of a primary alloimmune response, the source of minor RBC antigens in current practice is most likely RBC transfusions [47].…”
Section: Incidence Of Minor Rbc Antigen Alloimmunization In Various Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports describe only occasional instances of Rh D alloimmunization after Rh D-incompatible transplants. 1,2 We recently encountered a case of persistent anti-Rh D alloimmunization following allogeneic hematopoietic SCT, and reviewed our institutional experience for patients undergoing myeloablative conditioning and RIC allogeneic hematopoietic SCT to gain current insight regarding the incidence and potential clinical significance of Rh D alloimmunization in this setting.…”
mentioning
confidence: 99%
“…A patient with chronic myeloid leukemia developed a severe immune hemolytic anemia due to multiple RBC alloantibodies several weeks after allogeneic SCT [91]. De la Rubia et al [92] demonstrated an immunization rate of 3.7% for non-ABO RBC antibodies after allogeneic SCT. They observed antibody formation more frequently in ABO-mismatched cases, suggesting a potential role of this incompatibility in facilitating antibody production.…”
Section: Non-abo Blood Group Differences and Antibodiesmentioning
confidence: 99%